2014
DOI: 10.1186/s40623-014-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Coronal magnetic field and the plasma beta determined from radio and multiple satellite observations

Abstract: We derived the coronal magnetic field, plasma density, and temperature from the observation of polarization and intensity of radio thermal free-free emission using the Nobeyama Radioheliograph (NoRH) and extreme ultraviolet (EUV) observations. We observed a post-flare loop on the west limb 11 April 2013. The line-of-sight magnetic field was derived from the circularly polarized free-free emission observed by NoRH.The emission measure and temperature were derived from the Atmospheric Imaging Assembly (AIA) onbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Only recently have Iwai et al (2014) reported that their observation of coronal magnetic field and plasma pressure leads to a plasma beta that remains inconsistent with the minimum/maximum range given in Gary (2001); see the red square in Figure 1, where the size of the square indicates the uncertainty on the observed plasma beta value. Their observational results, on the other hand, fits nicely to our 10 -6 10 -4 10 -2 10 0 10 2 10 4 plasma beta [ -] 10 -1 active region data obtained from our MHD model: Even though their beta estimate is about one order of magnitude below the minimum value given in Gary (2001) (black dotted line), it is well within our average and minimum values obtained from the active region MHD model data (blue solid and dotted lines).…”
Section: Plasma Betamentioning
confidence: 78%
“…Only recently have Iwai et al (2014) reported that their observation of coronal magnetic field and plasma pressure leads to a plasma beta that remains inconsistent with the minimum/maximum range given in Gary (2001); see the red square in Figure 1, where the size of the square indicates the uncertainty on the observed plasma beta value. Their observational results, on the other hand, fits nicely to our 10 -6 10 -4 10 -2 10 0 10 2 10 4 plasma beta [ -] 10 -1 active region data obtained from our MHD model: Even though their beta estimate is about one order of magnitude below the minimum value given in Gary (2001) (black dotted line), it is well within our average and minimum values obtained from the active region MHD model data (blue solid and dotted lines).…”
Section: Plasma Betamentioning
confidence: 78%
“…. Thus, the conditions of V d ∼ V A and β ∼ 1 would generally be satisfied in the reconnection jet front regions when the process is driven by low-β upstream plasma as observed in Earth's magnetotail lobes [24] and estimated in the solar coronal loops [25,26]. Then, ω pe =ω ce is written as ω pe ω ce ∼ 3 n 1 cm −3…”
mentioning
confidence: 97%
“…During this event, however, the twin spacecraft STEREO A and B were separated from the Sun-Earth line by angles of 177°and 172°, respectively, making it difficult to find the inclination. From the images, however, the apparent inclination could be estimated (Iwai et al 2014) and was 2°for source S2 and about 25°for source LS. Thus, the actual heights of GMRT source S2 would be the same as the radial heights of ∼58 Mm or 1.08 R s , while the actual height of source LS would be 127 Mm or 1.18 R s .…”
Section: Appendix a Estimation Of Heights Of Gmrt Radio Sourcesmentioning
confidence: 99%